Wildlife Tourism Business: Conservation or Exploitation? - Agim Abdul Hakim; Taufik Abdullah (Universitas Pendidikan Indonesia, 2024)
Wildlife Tourism is never loose from conservation and exploitation’s controversy. Many people debate this matter on social media or formal forums. The research was conducted with the aim of solving the contradiction problem relating to Wildlife Tourism business. The approach in this study uses a qualitative literature review method. The results showed that: (1) there is no bold action and strong regulation from the government to follow up on the animal exploitation; (2) lack of awareness from business actors and general public regarding animal exploitation, which makes the assumption that the practice is normal; (3) there needs to be synergy among components in the Wildlife Tourism industry to address issues related to exploitation actions that threaten animal welfare. In conclusion, the concept of sustainable tourism can be the way for Wildlife Tourism practices to be exempt from exploitation actions.